STRATEGI PENGELOLAAN KEUANGAN KELUARGA: MENINGKATKAN LITERASI FINANSIAL GENERASI MILENIAL - Muhammad Mahfud; Mulyadi; S Pentanurbowo; Abdur Rahman (JOURNAL OF COMMUNITY DEDICATION, 2025)
The purpose of this research is to find out the Family Financial Management Strategy: Improving the Financial Literacy of the Millennial Generation. This research method is Type of Research: Qualitative This research is a type of literature research; This means that the information materials used come from library sources in the form of books, encyclopedias, magazines, journals, newspapers, journals, and others Approach: Case studies on millennial families, surveys of the millennial generation to measure the level of financial literacy, and literature analysis. The form of this research is descriptive, analytical, and critical. The results of this study are to summarize the importance of financial literacy in family financial management, especially for the millennial generation, as well as its impact on the quality of life and long-term financial well-being. This research can provide useful insights for many families, especially millennials who are struggling to adjust to an increasingly complex financial world.